Light-Induced Gasification of Fuels Prepared from Coal-Enrichment Wastes; Coke and Chemistry; Vol. 61, iss. 7 - Zaitsev A. S. Aleksandr Sergeevich; Tkachenko P. P. Pavel Petrovich; Belonogov M. V. Maxim Vladimirovich; Egorov R. I. Roman Igorevich (2018, 2018)
Title screen